Outcomes of TP53‐mutant acute myeloid leukemia with decitabine and venetoclax. Issue 20 (13th July 2021) - Kim, Kunhwa; Maiti, Abhishek; Loghavi, Sanam; Pourebrahim, Rasoul; Kadia, Tapan M.; Rausch, Caitlin R.; Furudate, Ken; Daver, Naval G.; Alvarado, Yesid; Ohanian, Maro; Sasaki, Koji; Short, Nicholas J.; et al.
Abstract : Background: TP53 mutation ( TP53 mut ) confers an adverse prognosis in acute myeloid leukemia (AML). Venetoclax with hypomethylating agents is a current standard for older patients; however, recent reports suggest that TP53 mut confers resistance to venetoclax. The authors investigated the outcomes of patients with TP53 mut AML who were treated with a 10‐day decitabine and venetoclax (DEC10‐VEN) (ClinicalTrials.gov identifier NCT03404193). Methods: Patients with newly diagnosed AML received decitabine 20 mg/m 2 for 10 days every 4 to 6 weeks for induction, followed by decitabine for 5 days after response. The venetoclax dose was 400 mg daily. TP53 mut was identified in bone marrow samples using next‐generation sequencing, with sensitivity of 5%. Outcomes were analyzed according to European LeukemiaNet 2017 guidelines. Results: Among 118 patients (median age, 72 years; age range, 49‐89 years), 63 (53%) had secondary AML, 39 (33%) had AML with complex karyotype, and 35 (30%) had TP53 mut AML. The median TP53 variant allele frequency was 32% (interquartile range, 16%‐65%), 8 patients (23%) had only a single TP53 mutation, 15 (43%) had multiple mutations, and 12 (34%) had mutation and deletion. Outcomes were significantly worse in patients who had TP53 mut AML compared with those who had wild‐type TP53 AML, with an overall response rate of 66% vs 89% ( P = .002), a complete response/complete response with incomplete hematologic recovery rate of 57% vs 77% ( P = .029), and a 60‐day mortality of 26% vs 4% ( P < .001), respectively. Patients with TP53 mut versus wild‐type TP53 had shorter overall survival at 5.2 versus 19.4 months, respectively (hazard ratio, 4.67; 95% CI, 2.44‐8.93; P < .0001), and shorter relapse‐free survival at 3.4 versus 18.9 months (hazard ratio, 4.80; 95% CI, 1.97‐11.69; P < .0001), respectively. Outcomes with DEC10‐VEN in patients with TP53 mut AML were comparable to historical results with 10‐day decitabine alone. Conclusions: Patients with TP53 mut AML have lower response rates and shorter survival with DEC10‐VEN. Abstract : Acute myeloid leukemia(AML) with TP53 mutations continues to be a therapeutic challenge and has been implicated as a resistance mechanism to venetoclax. Post‐hoc analysis of a prospective clinical trial of decitabine and venetoclax shows significantly lower response rate, overall survival, and relapse‐free survival in patients with TP53 ‐mutated compared with wild‐type AML.